Assessment of Features of Musculoskeletal Involvement in Children Diagnosed with Severe Sepsis: An Institutional Based Study - Ghanshyam G. Patel; Raj Krishna Goyal (Asian Journal of Medical Research, 2018)
Background: Sepsis represents the leading cause of mortality among infants and children globally. Hence; the present study was conducted to assess features of musculoskeletal involvement in children diagnosed with severe sepsis. Materials & Methods: 50 children under the age of twelve who exhibited disseminated infections were included in the study. Demographic information was gathered, and patients displaying clinical signs indicative of septic arthritis and acute osteomyelitis were assessed throughout their hospital stay following a comprehensive clinical evaluation. The hematological and biochemical profiles of these patients were analyzed. Musculoskeletal involvement was assessed in all the patients. Results: Mean age of the subjects was 11.8 years. 58 percent of the subjects were boys while the remaining were girls. Musculoskeletal involvement was seen in 60 percent of the subjects. Among these 30 subjects with musculoskeletal involvement, osteomyelitis was seen in 66.67 percent of the subjects while septic arthritis was seen in 33.33 percent of the subjects. Femur, Humerus, hip and shoulder involvement occurred in 33.33 percent, 26.67 percent, 16.67 percent and 10 percent of the patients respectively. Conclusion: The incidence of osteoarticular infections is notably elevated in pediatric patients with disseminated disease, necessitating a heightened clinical awareness for these conditions.